The role of marketing in the management of upbringing and education institution - Miletić, Josip, kroatist (Array, 2020)
The paper addresses the role of marketing in the management of upbringing and education institution. We analyzed the characteristics of upbringing and education seen as a public good as well as the characteristics of marketing seen as business philosophy and business function. Furthermore, the paper explains the compatibility of marketing and education analyzing the specifics of these two activities. We identified the problems the management of upbringing and education institution faces, which all can be resolved in a quality manner by marketing approach. Marketing of upbringing and education institution has an increasing role and importance, marketing approach being the basis for the effective functioning of upbringing and education institutions.